Direct oral anticoagulants compared with vitamin K antagonists for left ventricular thrombi systematic review and meta-analysis. (14th October 2021) - Costa, G; Saleiro, C; Neto, V; Goncalves, L; Teixeira, R
Abstract: Background: Left ventricular thrombus (LVT) is a serious complication primarily occurring in patients with LV dysfunction following large myocardial infarction. The role of direct oral anticoagulants in this clinical setting remains controversial. Purpose: To compare DOACs versus vitamin K antagonists (VKA) in LVT treatment. Methods: We systematically searched PubMed, Embase and Cochrane databases, in February 2020, for interventional or observational studies comparing DOAC with VKA on LVT treatment. Results: Fourteen publications were included, nine published studies and five conference abstracts, providing 1899 patients, 490 patients on DOACs and 1409 subjects on VKA. In terms of efficacy, DOAC had a lower LVT resolution for all studies included which reported LVT resolution (pooled OR, 0.73; 95% CI, 0.55–0.98; P=0.04; I 2 =52%), but sensitivity analysis revealed no difference between anticoagulant strategy (pooled OR, 0.78; 95% CI, 0.57–1.05; P=0.10; I 2 =59%). In terms of systemic embolism or stroke, DOAC had a similar efficacy (pooled OR, 1.06; 95% CI, 0.69–1.63; P=0.78; I 2 =30%) compared to VKA. In clinically relevant bleeding events analysis, the anticoagulation strategy did not differ in the odds of bleeding (pooled OR, 0.65; 95% CI, 0.37–1.15 P=0.14; I 2 =0%), with similar findings in net adverse clinical events analysis (pooled OR, 0.66; 95% CI, 0.35–1.25; I 2 =54%; P=0.20). Conclusion: Our pooled data suggests DOACs as a safe approach to LVT, despite inconsistent efficacy on LVT resolution. FUNDunding Acknowledgement: Type of funding sources: None.